Comparative effects of single-task and dual-task acute moderate-intensity exercise on cortisol and cognitive performance - Shao, Zhongshu; Peng, Jiazheng; Luo, Minggang; Zikereya, Talifu; Chen, Jinliang; Shi, Kaixuan (Frontiers in Psychology, 2025)
BackgroundAcute physical exercise elicits neuroendocrine responses that may transiently modulate cognitive performance. While moderate-intensity single-task exercise (e.g., running) has been shown to improve cognition, the acute cognitive and hormonal effects of dual-task exercise, which involves cognitive load, remain underexplored.ObjectivesThis study aims to compare the effects of moderate-intensity single-task (5-km run) and dual-task (orienteering) exercise on salivary cortisol levels and cognitive performance in healthy young adults.MethodsTwenty-one male college students (age: 20.57 ± 2.57 years) participated in a randomized crossover design. Each participant completed both exercise conditions. Salivary cortisol and cognitive performance (assessed via 2-Back, Mental Rotation, and Bells visual search tests) were measured before and after exercise. Exercise intensity was standardized using VO₂max, and heart rate was continuously monitored.ResultsOrienteering elicited a significant increase in salivary cortisol (p < 0.01), whereas 5-km run did not. Both exercises significantly improved reaction times (RTs) on the 2-Back and Mental Rotation tasks (p < 0.01), though no significant improvements in task accuracy were observed (p > 0.05). Performance on the Bells task improved post-exercise but showed no correlation with cortisol changes. Increases in cortisol were positively associated with RTs and accuracy improvements on working memory and spatial tasks, but not with visual search.ConclusionDual-task exercise induced stronger neuroendocrine responses and broader cognitive benefits compared to single-task running. These findings suggest that integrating cognitive demands into exercise routines may enhance acute cortisol-driven facilitation of executive functions, highlighting the importance of such exercises in programs targeting cognitive and brain health.